Accepting telemedicine in a circulatory medicine ward in major hospitals in South Korea: patients' and health professionals' perception of real-time electrocardiogram monitoring - Seo-Joon Lee; Tae-Young Jung; Tae-Ro Lee; Jae-Hoon Han (BMC, 2018)
Abstract Background South Korean government is currently in progress of expanding the coverage of telemedicine projects as part of an attempt to vitalize service industry, but is facing fierce opposition from KMA. Practice of telemedicine requires sufficient discussions among related parties. Although the participation of medical specialists is important, agreement from the public is essential. Methods Three main tertiary care centers in Seoul were selected for data collection. A total of 224 patients (patients n = 180, patient guardian n = 44) and medical professionals (n = 41) were selected using simple random sampling. Mixed method of quantitative survey and qualitative semi-interview was used. Results This study analyzed patients' and medical professionals' perception about the application of telemedicine in cardiology ward in tertiary care centers to provide baseline data when developing and applying telemedicine services. Results implied high need for encouraging telemedicine projects in order to appeal needs among population by providing experience (p < 0.001) and knowledge (p < 0.001). Other results showed that the need for electrocardiography monitoring was high among not only in remote areas but also in areas close to the capital. 64.52% of all participants thought that telemedicine was needed, and 73.21% of participants were willing to use telemedicine service if provided. Semi-interviews revealed that participants expected more cost and time saving services through remote treatment, by not having to visit long distance hospitals frequently. Conclusions Research results oppose Korean Medical Association's opinion that the population is against enforcing telemedicine related laws. The findings in this study reflect an up-to-date perception of telemedicine among patients and medical professionals in a tertiary care centers' cardiology ward. Moreover, the study provides a baseline that is needed in order to overcome past failures and to successfully implement telemedicine in South Korea.